2000
DOI: 10.1128/jvi.74.8.3874-3880.2000
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus-Induced Disruption of the Glial-Fibrillary-Acidic Protein Cytoskeleton in an Astrocytoma Cell Line (U-251)

Abstract: A recombinant measles virus which expresses enhanced green fluorescent protein (MVeGFP) has been used to infect two astrocytoma cell lines (GCCM and U-251) to study the effect of virus infection on the cytoskeleton. Indirect immunocytochemistry was used to demonstrate the cellular localization of the cytoskeletal components. Enhanced green fluorescent protein autofluorescence was used to identify measles virus-infected cells. No alteration of the actin, tubulin, or vimentin components of the cytoskeleton was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…large syncytia) in Vero cells infected with the Masusako strain, and Kouomou and Wild reported a similar finding (34). MV infection in human astrocytoma cells was described previously by Duprex et al (18,19). By means of an Edmonston-based recombinant virus construct that encoded green fluorescent protein, they showed that cell-to-cell spread took place through the cells' processes during early infection of GCCM cells (18) and that syncytia formed extensively in GCCM and U-251 cells (19).…”
Section: Infection Of Neural Cells With Sspe Virussupporting
confidence: 64%
See 1 more Smart Citation
“…large syncytia) in Vero cells infected with the Masusako strain, and Kouomou and Wild reported a similar finding (34). MV infection in human astrocytoma cells was described previously by Duprex et al (18,19). By means of an Edmonston-based recombinant virus construct that encoded green fluorescent protein, they showed that cell-to-cell spread took place through the cells' processes during early infection of GCCM cells (18) and that syncytia formed extensively in GCCM and U-251 cells (19).…”
Section: Infection Of Neural Cells With Sspe Virussupporting
confidence: 64%
“…MV infection in human astrocytoma cells was described previously by Duprex et al (18,19). By means of an Edmonston-based recombinant virus construct that encoded green fluorescent protein, they showed that cell-to-cell spread took place through the cells' processes during early infection of GCCM cells (18) and that syncytia formed extensively in GCCM and U-251 cells (19). Although they did not consider the role of the cell receptor in the infection process, CD46 is likely to be involved in this process.…”
Section: Infection Of Neural Cells With Sspe Virusmentioning
confidence: 99%
“…Duprex and colleagues demonstrated cell-to-cell spread of MV in astrocytoma cells, and MV infection caused disruption of the glial-fibrillary-acidic protein filament but not MTs (49,50). The implementation of these studies in various cell types is expected to elucidate the molecular mechanisms of MV pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The T‐cell attack may be mediated by autoimmunity or, as an attractive alternative, by viral infection of astrocytes. Various viruses can cause cytoskeleton alterations (8); for example, in vitro infection of astrocytoma cell lines with measles virus may disrupt the cytoskeleton (9), thus also offering a process for direct cell damage. Interestingly, HHV6‐mediated infection of astrocytes has been demonstrated in a population of patients with mesial TLE.…”
Section: Commentarymentioning
confidence: 99%